2003
DOI: 10.1161/01.cir.0000058700.41738.12
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations and Genetic Variation of Matrix Metalloproteinase 9 and Prognosis of Patients With Cardiovascular Disease

Abstract: for the AtheroGene InvestigatorsBackground-Matrix metalloproteinase (MMP)-9 secretion by macrophages and other inflammatory cells accelerates atherosclerotic progression and destabilizes vulnerable plaque in animal models. However, epidemiological data evaluating the prognostic impact of circulating concentrations and functional genetic variations of MMP-9 are lacking. Methods and Results-In a prospective study of 1127 patients with documented coronary artery disease, we measured baseline plasma MMP-9 levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

31
504
5
27

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 691 publications
(593 citation statements)
references
References 31 publications
31
504
5
27
Order By: Relevance
“…The role of metalloproteinases and their tissue inhibitor are still a matter of discussion in hypertension and cardiovascular disease. Although in atherosclerotic lesions and in patients with coronary artery disease, increased levels of metalloproteinases, in particular matrix metalloproteinases type 9, are associated with plaque vulnerability and rupture, 23 in hypertension most studies have found increased levels of TIMP-1 whereas metalloproteinases were normal or reduced. 15,25 In the process of vascular remodelling that takes place in hypertensives, a reduction in the ratio of metalloproteinases and TIMP-1 could be responsible for an increased extracellular matrix deposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of metalloproteinases and their tissue inhibitor are still a matter of discussion in hypertension and cardiovascular disease. Although in atherosclerotic lesions and in patients with coronary artery disease, increased levels of metalloproteinases, in particular matrix metalloproteinases type 9, are associated with plaque vulnerability and rupture, 23 in hypertension most studies have found increased levels of TIMP-1 whereas metalloproteinases were normal or reduced. 15,25 In the process of vascular remodelling that takes place in hypertensives, a reduction in the ratio of metalloproteinases and TIMP-1 could be responsible for an increased extracellular matrix deposition.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Moreover, in patients with coronary heart disease some of these serum markers have prognostic implications. [21][22][23] The aim of this study was to evaluate the correlation between the degree of endothelial dys-function, as measured by the maximal acetylcholine-induced forearm vasodilation, and the serum level of biochemical markers of inflammation, remodeling and oxidative stress, in a group of newly diagnosed, never-treated, essential hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Blankenburg et al (16) conducted a study in patients with existing coronary artery disease. They found that soluble MMP-9 measured in the blood provided the most efficient prognostic information beyond that offered by traditional prognostic markers such as cholesterol or other inflammatory markers.…”
Section: Mmps As Diagnostic or Prognostic Markersmentioning
confidence: 99%
“…It has been implicated in the remodelling processes associated with atherogenesis and plaque rupture (21,22). A strong association between baseline MMP-9 levels and future risk of cardiovascular mortality has been demonstrated in patients with documented coronary artery disease (23), suggesting that MMP-9 might constitute a novel biomarker for characterizing individuals at higher cardiovascular risk.…”
mentioning
confidence: 99%